An ontology-driven system architecture for precision agriculture applications. (2nd June 2009) - Goumopoulos, Christos; Kameas, Achilles D.; Cassells, Alan
Our research has been performed in the context of the EU-funded R&D project PLANTS. In this paper, we describe an ontology-driven architecture for developing systems that can be used in precision agriculture applications. Central to our approach is the use of an ontology, which views plants and associated computation as an integral part and allows the interaction of plants and artefacts in the form of synergistic mixed societies. PLANTS ontology sets up a conceptual framework that combines the knowledge about sensors, actuators and other domain concepts available, on the one hand, and the biological studies about plant stressing and sensing mechanisms and consequent plant behaviour, on the other hand, to make plants a proactive component of agricultural systems.